iTRAQ Proteomic Analysis of Interactions Between 20E and Phospholipase C in Apolygus lucorum (Meyer-Dür) - Tan, Yong-An; Zhao, Xu-Dong; Zhao, Jing; Zhu-Salzman, Keyan; Ji, Qin-Qin; Xiao, Liu-Bin; Hao, De-Jun (Frontiers in Physiology, 2022)
Polyphagous Apolygus lucorum has become the dominant insect in Bacillus thuringiensis (Bt) cotton fields. Hormone 20-hydroxyecdysone (20E) regulates multiple insect development and physiology events. 20E responses are controlled by pathways triggered by phospholipase C (PLC)-associated proteins. However, 20E-modulated genes and related proteins that can be affected by PLC still remain unknown. Here, isobaric tag for relative and absolute quantitation (iTRAQ) and immunoblotting techniques were used to compare differentially expressed proteins (DEPs) in A. lucorum in response to the treatment of 20E and the PLC inhibitor U73122 as well as their combination. A total of 1624 non-redundant proteins and 97, 248, 266 DEPs were identified in the 20E/control, U73122/control, and 20E+U73122/control groups, respectively. Only 8 DEPs, including pathogenesis-related protein 5-like, cuticle protein 19.8, trans-sialidase, larval cuticle protein A2B-like, cathepsin L1, hemolymph juvenile hormone-binding protein, ATP-dependent RNA helicase p62-like, and myosin-9 isoform X1, were detected in all three groups. KEGG enrichment analysis showed that the DEPs were involved in diverse signaling pathways. The results were validated by immunoblotting, which highlighted the reliability of proteomics analysis. These findings provided novel insights into the function of PLC in 20E signaling pathway in A. lucorum.